NILAI-NILAI PENDIDIKAN KARAKTER BERBASIS AL-QUR’AN - Nur Shofiati; Abdul Jalil; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This research in this digital age, many who study educational problems because they care about their interest in learning and trying to achieve success. What they want is their instant success spoiled by technological and informatics advancements, which are easily accessible to Indonesians, young and old alike, every day. This type of research is library research using descriptive methods and data analysis. The findings in this study indicate the relevance of the values of character education in the letter Ali-Imron verses 159-160 in Islamic religious education include : 1) Soft nature has relevance in Islamic religious education which creates comfortable comfort in the educational process, 2) forgiving has relevance in Islamic religious education for students who are good in the school and family environment because it supports morality for children, 3) Deliberation has been relevance in Islamic education increases feelings, understanding, love, and seriousness of public interests, 4) Tawakkal to God has relevance in Islamic education that is able to resist trials, or obstacles, 5) Trust in the arrival of God's help has relevance in Islamic religious education can lead to empathy for fellow human beings, parents, teachers and friends